Red tide detection using remotely sensed data: A case study of Sabah, Malaysia - Asmala Ahmad,; Noorazuan Hashim,; Laili Nordin, (Faculty of Social Sciences and Humanities, UKM,Bangi, 2009)
A red tide (RT) is composed of harmful blooms or algae that could cause mass mortalities of marine life and lead to human intoxications or even death. Several red-tide events have been reported in Sabah since 1976. The latest event occurred in February and March 2000 near the coastal waters of Sipitang Bay. This article examines the use of the RT image-processing algorithm through SPOT 4 satellite data application in detecting toxic blooms which occurred on February 2000. Results from the classified image indicate that SPOT 4 is capable of determining a possible red tide event quantitatively and spatially. It is estimated that about 40 km2 of the classified image was affected by RT. The occurrence of red tide was due to an increase of nitrate- and phosphorus- based nutrient loads discharge the aftermath of anthropogenically induced land use and land cover change near Sipitang-Beaufort area. This research suggests further investigations with detailed land cover information to demarcate inorganic sources, as well as a field survey of seawater quality conditions